Labor Market Aspects of Industrial Restructuring in Canada - Prasad, Eswar (IMF Working Papers; Working Paper ;, 1993)
This note examines recent developments in the Canadian labor market to provide a partial assessment of the magnitude and nature of industrial restructuring in Canada. The implications of industrial restructuring for the medium- and long-term prospects for the Canadian economy are examined. The evidence presented in this note suggests that the recent increases in labor productivity may represent a cyclical phenomenon rather than a permanent increase in the rate of growth of productivity.